Small size, big problems: insights and difficulties in prenatal diagnosis of fetal microcephaly - Haddad, Leila; Hadi, Efrat; Leibovitz, Zvi; Lev, Dorit; Shalev, Yoseph; Gindes, Liat; Lerman-Sagie, Tally (Frontiers in Neuroscience, 2024)
Microcephaly is a sign, not a diagnosis. Its incidence varies widely due to the differences in the definition and the population being studied. It is strongly related to neurodevelopmental disorders. Differences in definitions and measurement techniques between fetuses and newborns pose a great challenge for the diagnosis and prognostication of fetal microcephaly. A false positive diagnosis can result (in countries where it is legal) in erroneous termination of pregnancy, where a false negative diagnosis might lead to the birth of a microcephalic newborn. Microcephaly in growth restricted fetuses deserves special attention and separate evaluation as it is an important prognostic factor, and not necessarily part of the general growth retardation. Several genetic syndromes incorporating microcephaly and intrauterine growth retardation (IUGR) are discussed. Deceleration of the head circumference (HC) growth rate even when the HC is still within normal limits might be the only clue for developing microcephaly and should be considered during fetal head growth follow up. Combining additional parameters such as a positive family history, associated anomalies, and new measurement parameters can improve prediction in about 50% of cases, and thus should be part of the prenatal workup. Advances in imaging modalities and in prenatal genetic investigation along with the emergence of new growth charts can also improve diagnostic accuracy. In this article, we review the different definitions and etiologies of fetal microcephaly, discuss difficulties in diagnosis, investigate the reasons for the low yield of prenatal diagnosis, and provide improvement suggestions. Finally, we suggest an updated algorithm that will aid in the diagnosis and management of fetal microcephaly.